Iteration A = 0
Iteration A = 1
Iteration B i = 0 j = 0 k = 0
Iteration B i = 0 j = 0 k = 1
Iteration B i = 0 j = 0 k = 2
Iteration B i = 0 j = 0 k = 3
Iteration B i = 0 j = 1 k = 0
Iteration B i = 0 j = 1 k = 1
Iteration B i = 0 j = 1 k = 2
Iteration B i = 0 j = 1 k = 3
Iteration B i = 0 j = 2 k = 0
Iteration B i = 0 j = 2 k = 1
Iteration B i = 0 j = 2 k = 2
Iteration B i = 0 j = 2 k = 3
Iteration B i = 1 j = 0 k = 0
Iteration B i = 1 j = 0 k = 1
Iteration B i = 1 j = 0 k = 2
Iteration B i = 1 j = 0 k = 3
Iteration B i = 1 j = 1 k = 0
Iteration B i = 1 j = 1 k = 1
Iteration B i = 1 j = 1 k = 2
Iteration B i = 1 j = 1 k = 3
Iteration B i = 1 j = 2 k = 0
Iteration B i = 1 j = 2 k = 1
Iteration B i = 1 j = 2 k = 2
Iteration B i = 1 j = 2 k = 3